Benchmarking pangenome dynamics and horizontal gene transfer in Mycobacterium marinum evolution - Shahed, Khandker; Islam, Sk Injamamul; Sangsawad, Papungkorn; Jung, Won-Kyo; Permpoonpattana, Patima; Linh, Nguyen Vu (Frontiers in Microbiology, 2025)
Horizontal gene transfer (HGT) is a key driver of microbial evolution, promoting genetic diversity and contributing to the emergence of antibiotic resistance. This study explores the pangenome dynamics and HGT in Mycobacterium marinum (M. marinum), a close relative of Mycobacterium tuberculosis. Multiple pangenome datasets were analyzed to quantify gene gain, loss, and pangenome openness, utilizing Panstripe and a Generalized Linear Model (GLM) framework to assess gene presence/absence across strains. Additionally, a comparative benchmarking analysis of gene ontology (GO) annotations were conducted using eggNOG and InterProScan to evaluate their functional annotation accuracy. Our findings demonstrated significant differences in gene gain and loss rates, suggesting variations in annotation accuracy and the presence of mobile genetic elements (MGE). Single nucleotide polymorphisms (SNPs) were also identified, highlighting the genetic variability that may impact strain-specific traits such as pathogenicity and antibiotic resistance. Pangenome of M. marinum was characterized as highly open, with substantial variability in gene content, reflecting ongoing genetic exchange and adaptability. Functional annotation benchmarking demonstrated that eggNOG and InterProScan provided complementary insights, with each tool excelling in distinct strengths of gene function identification. Overall, these findings highlight the complex interplay between HGT, pangenome evolution, and antibiotic resistance in M. marinum, and the analytical framework presented here provides a robust approach for future studies aiming to inform therapeutic interventions and vaccine development.